An Unusual Initial Presentation of Diffuse Large B-Cell Lymphoma as Recurrent Syncope. (27th December 2019) - Kim, Kunhwa; Kaur, Harpreet; Chan, Matthew; Balasubramanian, Manju; Gupta, Sorab; Jorge, Vinicius M.
Abstract : We describe a rare presentation of diffuse large B-cell Lymphoma (DLBCL) with recurrent episodes of syncope. During the workup for syncope, the patient was incidentally found to have an extensive mass in the left thorax, which was later diagnosed as stage 2 bulky disease DLBCL. This is the rare case of lymphoma presenting as recurrent syncope without cardiac involvement. The patient did not have any further episodes of syncope after her successful treatment of DLBCL.